Sorption characteristics and mechanisms of oxyanions and oxyhalides having different molecular properties on Mg/Al layered double hydroxide nanoparticles - Goh, Kok Hui (2012)
The sorption ability of fast-coprecipitated and hydrothermally-treated Mg/Al layered double hydroxide nanoparticles (FCHT-LDH) for various oxyhalides and oxyanions was evaluated. Interactions of oxyhalide such as monovalent bromate or oxyanions such as divalent chromate and divalent vanadate with FCHT-LDH were investigated using a combination of macroscopic (batch sorption/desorption studies and electrophoretic mobility (EM) measurements) and microscopic techniques (CHNS/O, XRD, FTIR, XPS, and EXAFS analyses). The sorption studies on various oxyanions and oxyhalides suggested that their sorption characteristics on FCHT-LDH were largely governed by their ionic potentials and molecular structures. Oxyanions which have ionic potentials higher than 7 nm−1 were found to be more readily sorbed by FCHT-LDH than oxyhalides with ionic potentials lower than 5 nm−1. The results obtained also demonstrated that trigonal pyramid oxyhalides showed a lower degree of specificity for FCHT-LDH than the tetrahedral coordinated oxyanions. From the macroscopic and microscopic studies, monovalent oxyhalide sorption on FCHT-LDH was postulated to occur mainly via anion exchange mechanism with subsequent formation of outer-sphere surface complexes. For polyvalent oxyanion sorption on FCHT-LDH, the mechanisms were possibly associated with both anion exchange and ligand exchange reactions, resulting in the coexistence of outer-sphere and inner-sphere surface complexes.